Conservative management of unilateral and unilocolor ovarian cysts ≥ 10 cm in diameter in postmenopausal women - Mehmet Serdar Oguz; Tolga Ecemiş; Gülçin T. Sarıyıldız (IMR Press, 2021)
Objective: To evaluate and follow up the native behaviour of large ovarian cysts in postmenopausal women and establish the best approach based on advanced imaging technology. Study Design: The number of patients that were evaluated from January 2015 to September 2019 were 417. At the end of this study period, 375 patients were considered for this prospective evaluation. The patients with an ultrasound diagnosis of unilateral and unilocular ovarian cysts with regular septa ≥ 10 cm in diameter at menopause were enrolled in this study. During the follow-ups, the patients who developed irregular or thick septa, papillary formation or solid areas, exhibited any suspicious sign of malignancy in magnetic resonance imaging (MRI) results or displayed an augmentation in CA-125 levels were excluded from the study. In this study cancer antigen-125 (CA-125) values > 65 IU/mL were considered abnormal. The patients who met these criteria were followed with periodical ultrasounds and yearly MRI. Results: The 42 patients who were excluded from the study had significant morphological changes. These patients were showing an increase in CA-125 levels along with abnormal MRI findings during the follow-ups and in addition, they had surgical removal of cysts. All the significant morphological changes were detected by transvaginal ultrasounds. Postoperative histopathological diagnosis of these ovarian cysts revealed no abnormality. From 375 patient's cysts samples one hundred and twenty-five (33.3%) cysts had significantly decrease in size, one hundred and eleven (29.6%) of the cysts had spontaneous resolution and one hundred thirty-nine (37%) cysts persistently remained unchanged during the follow up period. The diameter of the cysts ranged from 10.4 to 18.4 cm. The cysts were categorized into three groups corresponding to a range of diameters i.e., 10-12.9 cm (62%), 13-15.9 cm (24.1%) and ≥ 16 cm (13.8%) respectively. The patients who showed spontaneous resolution were discontinued with the follow-ups while the rest of the patients were continued with their regular follow up examinations. Conclusion: The cysts should be monitored conservatively as long as possible before proceeding to a surgical treatment regardless of the size of the unilateral and unilocular ovarian cysts at postmenopausal period with limited oncogenic potential and without significant morphological changes.